Emotional and contemplative culture of life: the paradox of revealing the basics - Harutyunyan, Edvard (Bulletin of Yerevan University E: Philosophy, Psychology, 2022)
In the article, the culture of organization and regulation of everyday life is considered as an empirical ideology that reflects the civilized spirit of the people at the social level, the spirit of identity at the cultural level and the spirit of experience at the psychological level. Some features of the organization of the Armenian society at the levels of the soul (emotional objectivity) and spirit (contemplative objectivity) are also considered.
Keywords: culture of life; empirical ideology; national identity; world of ancestors; ethno-cultural refuge; emotional objectivity; deliberative objectivity; paradox of fundamentals